Technology‐mediated learning theory. (18th March 2019) - Bower, Matt
Abstract: Technology‐enhanced learning research, such as that relating to the use of online technologies in formal learning contexts, is sometimes criticised for being under‐theorised. This paper draws together areas of research and theory that have previously been somewhat separately treated, to support the integrated analysis and research of situations where technology mediates learning. First, key areas of research and theory relating to technology‐mediated learning are introduced, along with their associated conceptual underpinnings and assumptions, in terms of premises. These areas are then explained with relation to one another regarding how they can be used to holistically understand learning in contexts where technology mediates learning. The implications of the theoretical concepts are discussed in terms of the future conduct of technology‐mediated learning research, as well as the scope and conditions under which the theorisations apply.